IPTEKS PENGHITUNGAN SIKLUS HIDUP PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN TERBUKA DI BURSA EFEK INDONESIA) - Pontoh, Irene Florensia (Universitas Sam Ratulangi, 2019)
Rapid growth of economics makes many firms continue to develop their business. Along with the rapid growth of business the high competition rising between firms in term to snatch the market or consumers. The higher of competition gives an impact to firms life cycle which makes many firms keep develop their business strategy to attract the investors and consumers. Under assumption that the median is 0.76 based on sample, the result of calculation of the retained earnings to total equity (RETE) in period of 2016 shows that life cycle of each firms are varies. The result shows that firms under median are not at mature stage while firms above median are categorized as mature firms.